Study Of Centrifugal Pump Performance - Yaacob, Norizal (UTeM, 2009)
Centrifugal pump is the most important equipment and extensively used in all industrial plants where fluid handling is involved. The operation of a centrifugal pump is solely depends on its own flow-head characteristic curve. The operating point is always where the pump curve meets the flow-head system resistance curve of pumping system that particular pump is handling. Hence the importance of using those curves and the calculation to determine the operating point parameters cannot be overemphasized. Selecting the right pump for any application and the right manufacturer are two of the most important decisions that will have to make for the life of the product. Poor pump selection is the major contributor to the failure of processes that demand reliable fluid movement. In this project pump performance is investigated with certain experiment like series and parallel and result will be analyzed by plotting graph flow capacity against head to calculate pump efficiency.